Freezing Out Injustice: Using ICE to Foster Democratic Inquiry. (1st October 2016) - Taylor, Monica; Klein, Emily J.; Carletta, Liz
Abstract: In an urban teacher residency program, preservice science teachers experience what it's like to teach for social justice through the use of a democratic inquiry stance, thus moving toward an understanding of teaching for social justice as larger than one individual teacher in a classroom .